2003
DOI: 10.1063/1.1564862
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of YMnO3 epitaxial films for ferroelectric-gate field-effect transistors

Abstract: Ferroelectric properties of YMnO3 epitaxial films were studied. The ferroelectric properties of epitaxially grown (0001) YMnO3 films on (111)Pt/(0001)sapphire (epi-YMO/Pt) with an excellent crystallinity were compared to (0001)-oriented poly crystalline films on (111)Pt/ZrO2/SiO2/Si. The epi-YMO/Pt had saturated polarization–electric-field (P–E) hysteresis loops, with a remanent polarization (Pr) of 1.7 μC/cm2 and a coercive field (Ec) of 80 kV/cm. The fatigue property showed no degradation up to 1010 measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
62
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 28 publications
4
62
0
Order By: Relevance
“…Both YMnO 3 and GaN have hexagonal symmetry and have a nominal lattice mismatch of about 4% (to half the lattice constant of YMnO 3 ). We observe an unexpected 30° rotation between the two unit cells, resulting in a much larger lattice mismatch of ~10 %.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both YMnO 3 and GaN have hexagonal symmetry and have a nominal lattice mismatch of about 4% (to half the lattice constant of YMnO 3 ). We observe an unexpected 30° rotation between the two unit cells, resulting in a much larger lattice mismatch of ~10 %.…”
mentioning
confidence: 99%
“…We observe an unexpected 30° rotation between the two unit cells, resulting in a much larger lattice mismatch of ~10 %. To understand these results, we have carried out first principles calculations of the elastic energy of highly strained YMnO 3 . Because the relative stability of the first 1-2 layers determines the orientation of subsequent layers, we focus our calculations on the first unit cell at the interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, towards the integration of ferroelectric YMO into devices, epitaxial films onto suitable bottom electrodes must be developed. Indeed, Ito et al [5] have earlier reported the epitaxy of YMO(0 0 0 1) films on Pt(1 1 1)/Al 2 O 3 (0 0 0 1). Although the polarization P(E) loops of these films were better that those of polycrystalline YMO films, squarer P(E) loops are required [5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Ito et al [5] have earlier reported the epitaxy of YMO(0 0 0 1) films on Pt(1 1 1)/Al 2 O 3 (0 0 0 1). Although the polarization P(E) loops of these films were better that those of polycrystalline YMO films, squarer P(E) loops are required [5]. Film microstructure plays a fundamental role on the ferroelectric properties and detailed structural studies on hexagonal YMO hexagonal films is still lacking.…”
Section: Introductionmentioning
confidence: 99%